Sub-lethal stress-induced cross-protection against ultraviolet-C in Salmonella enterica on raw whole almonds and fresh-cut leafy greens - Chen, Zhao; Zheng, Jie; Micallef, Shirley A.; Meng, Jianghong (Frontiers in Microbiology, 2025)
Pre-exposure to sub-lethal stress can increase the resistance of foodborne pathogens to inactivation processes, posing potential risks to food safety. This study examined how sub-lethal stress influences the resistance of Salmonella enterica to ultraviolet-C (UV-C) treatments on raw whole almonds (RWAs) and fresh-cut leafy greens (FCLGs), investigated the role of rpoS in stress-induced cross-protection, and evaluated Enterococcus faecium NRRL B-2354 as a surrogate for S. enterica. Additionally, we assessed the survival of sub-lethally stressed cells on FCLGs under cold or temperature abuse condition post-UV-C treatment. A cocktail of three S. enterica strains, along with S. Typhimurium ATCC 14028 and its ΔrpoS mutant (IB43), were exposed to desiccation stress, heat shock, oxidation stress, or acid stress. Afterward, stressed and unstressed cells were inoculated onto RWAs and FCLGs, and treated with UV-C (500 μW/cm2, 60 min). Treated FCLGs were then stored under cold or temperature abuse condition for 7 days. Results showed that acid-stressed S. enterica exhibited greater UV-C resistance on RWAs, while oxidation-stressed cells had increased survival on FCLGs (p < 0.05). Under temperature abuse, unstressed, oxidation-stressed, or acid-stressed S. enterica were inactivated faster, whereas heat-shocked cells persisted until Day 7. Desiccation-stressed cells rebounded temporarily before inactivation by Day 7. IB43 was more susceptible to UV-C (p < 0.05) than the wild-type strain and lacked cross-protection from prior sub-lethal stress exposure, confirming the crucial role of rpoS in UV-C resistance and stress adaptation. NRRL B-2354 demonstrated comparable or greater survival than S. enterica, supporting its use as a suitable surrogate. These findings highlight the influence of sub-lethal stress on UV-C resistance in S. enterica and emphasize the importance of including stress-adapted pathogens in challenge studies to improve food safety.